PENGARUH PENERAPAN METODE STAD TERHADAP HASIL BELAJAR EKONOMI DITINJAU DARI MINAT SISWA DI SMA N 10 BATANGHARI - Suratno, Suratno (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
The purpose of this study was to prove the effect of the acquisition methodSTAD student learning outcomes in terms of aspects of student interest in economicsubjects in class X at SMAN 10 Batang Jambi. The study was conducted using a quasiexperimentaldesign with one-shoot method of post test design. The results showed thatthe method STAD significant positive effect on the acquisition of student learningoutcomes. Proven to strengthen students' interest in learning method STAD acquisitionof student learning outcomes.